Efektivitas Model RMS (Reading, Mind Mapping, and Sharing) terhadap Peningkatan Hasil Evaluasi Pembelajaran Balāgah Mahasiswa - Said, Azizah Saad; Mahmudah, Mahmudah; Muhajir, Muhajir; Abduh, Indra Mahendra (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aims to test the effectiveness of the RMS (Reading, Mind Mapping, and Sharing) model in improving the evaluation results of Balāgah learning. This study used a quantitative method with a quasi-experimental design. The population consisted of Arabic Language Education students at UIN Sunan Kalijaga and a sample of 28 students was purposively selected from one class that met the criteria for full RMS implementation. Data were obtained from Balāgah learning evaluations given as pretests and posttests, supported by instruments that had passed expert validation and reliability testing. Data were collected through written tests and analyzed using descriptive statistics, paired sample t-tests, and Cohen's d to measure effect sizes. The results showed a highly significant improvement in students' evaluation performance, indicated by an increase in the average score from 53.79 to 83.43, a significant paired t-test result (p < 0.001), and a Cohen's d effect size of 4.52, which is categorized as very large. These results confirm that strengthening reading skills, visualizing concepts through mind maps, and engaging in collaborative sharing activities can improve students' analytical understanding. Therefore, the RMS model has proven to be effective for use in Balāgah learning.